Nucleotide‐Binding Oligomerization Domain‐Like Receptor Protein 3 Deficiency in Vascular Smooth Muscle Cells Prevents Arteriovenous Fistula Failure Despite Chronic Kidney Disease. Issue 1 (8th January 2019) - Ding, Xiangchao; Chen, Jiuling; Wu, Chuangyan; Wang, Guohua; Zhou, Cheng; Chen, Shanshan; Wang, Ke; Zhang, Anchen; Ye, Ping; Wu, Jie; Chen, Shanshan; Zhang, Hao; et al.
Abstract : Background: The arteriovenous fistula (AVF) is the preferred hemodialysis access for patients with chronic kidney disease. Chronic kidney disease can increase neointima formation, which greatly contributes to AVF failure by an unknown mechanism. Our study aimed to determine the role of nucleotide‐binding oligomerization domain‐like receptor protein 3 (NLRP3) in neointima formation induced by experimental AVFs in the presence of chronic kidney disease. Methods and Results: From our findings, NLRP3 was upregulated in the intimal lesions of AVFs in both uremic mice and patients. Smooth muscle–specific knockout NLRP3 mice exhibited markedly decreased neointima formation in the outflow vein of AVFs. Compared with primary vascular smooth muscle cells isolated from control mice, those isolated from smooth muscle–specific knockout NLRP3 mice showed compromised proliferation, migration, phenotypic switching, and a weakened ability to activate mononuclear macrophages. To identify how NLRP3 functions, several small‐molecule inhibitors were used. The results showed that NLRP3 regulates smooth muscle cell proliferation and migration through Smad2/3 phosphorylation rather than through caspase‐1/interleukin‐1 signaling. Unexpectedly, the selective NLRP3‐inflammasome inhibitor MCC950 also repressed Smad2/3 phosphorylation and relieved chronic kidney disease–promoted AVF failure independent of macrophages. Conclusions: Our findings suggest that NLRP3 in vascular smooth muscle cells may play a crucial role in uremia‐associated AVF failure and may be a promising therapeutic target for the treatment of AVF failure.